Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/ppul.24122
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disordered breathing and ventilatory support in children with Down syndrome

Abstract: Our results confirm the high prevalence of OSAS in children with DS. A significant number also have low baseline saturations, central apnoeas, and nocturnal hypoventilation. Contrary to popular belief, more than half of children with DS had satisfactory adherence to respiratory support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 27 publications
(38 reference statements)
4
58
0
1
Order By: Relevance
“…Consistent with previous research, swallowing dysfunction was common in this cohort of children with DS. Decreased airway protection resulting in DLP and/or aspiration was found in 31.9% of infants less than 6 months and in 51.3% of infants 6 to 12 months.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous research, swallowing dysfunction was common in this cohort of children with DS. Decreased airway protection resulting in DLP and/or aspiration was found in 31.9% of infants less than 6 months and in 51.3% of infants 6 to 12 months.…”
Section: Discussionsupporting
confidence: 91%
“…In a large observational study, Yang and colleagues found that the risk of death from aspiration, pneumonia, or influenza for individuals with DS was more than seven times that of the general population . Multiple factors contribute to this risk including the high prevalence of congenital airway and lung abnormalities, obstructive sleep apnea, pulmonary hypertension, and dysphagia . Bronchiectasis, structural lung disease, and airway inflammation can be seen in any child with dysphagia and chronic aspiration from a young age .…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with DS also have a high prevalence of CSA, nocturnal hypoventilation, and low overnight oxygen saturation compared with the general population. 6 The presence of SDB in patients with PWS is equally well recognized. CSA and hypoventilation are mainly seen in infants, while OSA is significantly more prevalent in older children (>2 years).…”
Section: Discussionmentioning
confidence: 99%
“…The age of the mother is an important risk factor for the nondisjunction of chromosome 21, so DS occurs more frequently in older mothers (Patterson, ; Sherman, Freeman, Allen, & Lamb, ). The phenotype of DS is variable (Patterson, ), and patients present clinical and physical features including facial dysmorphology, low muscle tone, short stature, intellectual disability and sleep‐disordered breathing (Karmiloff‐Smith et al, ; Trucco et al, ). Congenital heart diseases (CHD) are considered to be the most important clinical phenomenon in children with DS (Pfitzer et al, ).…”
Section: Introductionmentioning
confidence: 99%